Large-Signal Performance Optimization of Inverted-F Antenna Tuned by Switchable RF Capacitor - Solomko, Valentyn; Özdamar, Oguzhan; Weigel, Robert; Hagelauer, Amelie (2021 IEEE-APS Topical Conference on Antennas and Propagation in Wireless Communications, APWC 2021, 2021)
Harmonics emission by an aperture-tuned IFA (inverted-F antenna) is studied. The analytical analysis is conducted using a transmission-line model of the antenna. Based on the results of analysis, an optimization example for the large-signal performance of a carrier-aggregation front-end tuned by a high-voltage switchable RF capacitor is presented, the findings are supported by the measurements on a hardware demonstrator. According to the experimental results, the power of a second harmonic at 1800 MHz coupled from the main into diversity antenna is reduced by 10 dB by fine-selecting the position of the capacitor-based tuning network along the radiating element of the main antenna.
CRIS-Team Scopus Importer:2021-10-15
Keywords: antenna tuning; aperture tuning; C-tuner; carrier aggregation; cellular user equipment; harmonics; high-voltage RF switch; inverted-F antenna; RF switch; switchable capacitor; user terminal